Effect of Dynamic Fluid Module Based on Information and Communication Technologies (ICT) on Science Process Skills and Learning Outcomes for High School Students - Rizha Yulinda Salsabila; Subiki Subiki; Maryani Maryani (Pancaran Pendidikan, 2020)
ICT-based dynamic fluid modules are efficient ICT-based teaching materials that have the appeal of students to be more motivated, active more able to understand the concept of dynamic fluid material. The purpose of this research is to know the influence of the use of ICT-based dynamic fluid modules on science process skills and student learning outcomes in high school. The type of research used in is experimental research with the design of post-test only control group. Scsience Process skills score and student learning outcomes show significant differences between experimental classes and control classes.